Late Quaternary environments of Nicholas Swamp, Nicholas Range, eastern Tasmania/Lutruwita, Australia - Patrick T. Moss; Amirah Farrell; Sebastian Martin-Wallace; Peter D. McIntosh; Adrian Slee; Quan Hua; Kevin Welsh; Khairun Nisha Mohamed Ramdzan (Quaternary International, 2026)

The need to harmonise environmental sustainability assessments for pharmaceuticals - Caroline T.A. Moermond; Fiona Adshead; Stefan Berggren; Thea Skafte Böttcher; Marco Cinelli; Ruben de Moor; Yasmin de Wit; Mira Dysgård; Dirk Halet; Arne Hein; Katharina Högdin; Aline Katzenberger; et al. (Sustainable Chemistry and Pharmacy, 2026)

Serum cortisol concentrations in newborn foals are increased by transfusion with anti-rhodococcal hyperimmune plasma and inversely associated with immunoglobulin activity - Kira C. Sayre; Patricia Flores-Ahlschwede; Alexandra B. Wethington; Susanne K. Kahn; Jocelyne M. Bray; Devynn M. Volding; Scott Ahlschwede; Angela I. Bordin; Noah D. Cohen; Thomas H. Welsh (Journal of Equine Veterinary Science, 2026)

Analysis of nonsynonymous SNPs in candidate genes that influence bovine temperament and evaluation of their effect in Brahman cattle - Gilberto Ruiz-De-La-Cruz; Ana María Sifuentes-Rincón; Francisco Alejandro Paredes-Sánchez; Gaspar Manuel Parra-Bracamonte; Eduardo Casas; David G. Riley; George A. Perry; Thomas H. Welsh; Ronald D. Randel (Molecular Biology Reports, 2024)
Background Temperament is an important production trait in cattle and multiple strategies had been developed to generate molecular markers to assist animal selection. As nonsynonymous single nucleotide polymorphisms are markers with the potential to affect gene functions, they could be useful to predict phenotypic effects. Genetic selection of less stress-responsive, temperamental animals is desirable from an economic and welfare point of view. Methods and results Two nonsynonymous single nucleotide polymorphisms identified in HTR1B and SLC18A2 candidate genes for temperament were analyzed in silico to determine their effects on protein structure. Those nsSNPs allowing changes in proteins were selected for a temperament association analysis in a Brahman population. Transversion effects on protein structure were evaluated in silico for each amino acid change model, revealing structural changes in the proteins of the HTR1B and SLC18A2 genes. The selected nsSNPs were genotyped in a Brahman population ( n = 138), and their genotypic effects on three temperament traits were analyzed: exit velocity, pen score, and temperament score. Only the SNP rs209984404-HTR1B (C/A) showed a significant association ( P = 0.0144) with pen score. The heterozygous genotype showed a pen score value 1.17 points lower than that of the homozygous CC genotype. Conclusion The results showed that in silico analysis could direct the selection of nsSNPs with the potential to change the protein. Non-synonymous single nucleotide polymorphisms causing structural changes and reduced protein stability were identified. Only rs209984404-HTR1B shows that the allele affecting protein stability was associated with the genotype linked to docility in cattle.

Chronology and evolution of the world's largest sand island: K'gari (Fraser Island), South East Queensland, Australia - J. Shulmeister; T.M. Rittenour; N.R. Patton; D. Ellerton; A. Gontz; P.A. Hesp; T. Santini; G. Miot da Silva; S. Forman; H. Bowyer; J.T. Kelly; A. McCallum; et al. (Quaternary Science Reviews, 2024)

Monitoring population-level foraging distribution of a marine migratory species from land: strengths and weaknesses of the isotopic approach on the Northwest Atlantic loggerhead turtle aggregation - Simona A. Ceriani; Susan Murasko; David S. Addison; David Anderson; Greg Curry; Nicole A. Desjardin; Scott F. Eastman; Daniel R. Evans; Nancy Evou; Mariana M. P. B. Fuentes; Matthew H. Godfrey; Kristen M. Hart; et al. (Frontiers in Marine Science, 2023)
Assessing the linkage between breeding and non-breeding areas has important implications for understanding the fundamental biology of and conserving animal species. This is a challenging task for marine species, and in sea turtles a combination of stable isotope analysis (SIA) and satellite telemetry has been increasingly used. The Northwest Atlantic (NWA) loggerhead ( Caretta caretta ) Regional Management Unit, one of the largest sea turtle populations in the world, provides an excellent opportunity to investigate key biological patterns as well as methodological aspects related to the use of stable isotopes to infer spatial distribution of turtles in foraging areas. We provide the first comprehensive assessment of the annual distribution of NWA adult female loggerheads among foraging areas and investigate the efficacy of various analytical approaches as well as the effect of sample size in these types of studies. A total of 5168 individual females were sampled from seven Management Units (MUs) between 2013-2018. We provide the first estimate of the proportion of females originating from each MU that uses each foraging area and show how this proportion varies over time. We also estimate the relative importance (in terms of number of turtles) of each foraging area to the overall loggerhead breeding aggregation nesting in Florida and in the NWA for each year of the study. The foraging area used by reproductively active females differs considerably across MUs. One of these, the Subtropical NWA, is by far the most important foraging area in terms of both number of individuals and genetic diversity, and therefore this region may be considered as a conservation priority. Through simulations, we show that limited sizes of sample groups (unknowns; training; priors) may result in false geographic differentiation and consequently mislead interpretations. We provide thresholds and methodological recommendations for future studies. This study establishes a fundamental baseline for monitoring the annual contribution of foraging area to a terrestrial-based breeding aggregation of a marine animal in a cost-effective way. This type of monitoring allows for early detection of changes in foraging distributions—a possible effect of climate change on marine ecosystems or of area-specific anthropogenic threats.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Insights from a novel, user-driven science transfer program for resource management - J. L. M. Hinderer; Z. Blevins; S. J. Cooke; E. Dunlop; K. F. Robinson; D. L. Stang; T. J. Stewart; J. T. Tyson; A. B. Welsh; N. Young; A. M. Muir (Socio-Ecological Practice Research, 2021)
Research results are often not easily accessible or readily digestible for decision-making by natural resource managers. This knowledge-action gap is due to various factors including the time lag between new knowledge generation and its transfer, lack of formal management structures, and institutional inertia to its uptake. Herein, we reflect on the Great Lakes Fishery Commission’s Science Transfer Program and its evolution from ‘Mode 1’ (i.e., scientists conduct research autonomously) toward ‘Mode 2’ (i.e., co-production of knowledge with practitioners) knowledge production to understand and overcome the knowledge-action gap. Six success factors and strategies and tactics used to achieve those factors were critical to the shift from Mode 1 to Mode 2: (1) dedicate funding and staff support; (2) obtain top-down commitment from organizational leadership; (3) break down silos; (4) build relationships through formal and informal interactions; (5) emphasize co-production in program and project implementation; and (6) obtain buy-in among relevant actors. By way of three project case studies, we highlight knowledge transfer approaches, products, and lessons learned. We anticipate this contribution will benefit those working on knowledge mobilization, particularly in boundary-spanning organizations, and those involved in resource program management, administration, and design; it is also intended for resource managers seeking to have their science and information needs met more effectively.

Denitrification, anammox, and dissimilatory nitrate reduction to ammonium across a mosaic of estuarine benthic habitats - Jian‐Jhih Chen; Dirk V. Erler; Naomi S. Wells; Jianyin Huang; David T. Welsh; Bradley D. Eyre (Limnology and Oceanography, 2021)
Estuaries play a key role in moderating the flow of nitrogen (N) to marine ecosystems. However, the magnitude of this N removal can vary dramatically both within and between estuaries due to the benthic habitats present. Here, we compare denitrification, coupled nitrification–denitrification, anammox, and dissimilatory nitrate reduction to ammonium (DNRA) across a mosaic of benthic habitats in the subtropical Noosa River Estuary, Australia. Using 15 N tracer techniques and passive pore‐water samplers, we show that coupled nitrification–denitrification was the dominant pathway for N 2 production across all habitats, with higher rates in vegetated habitats (10–70 μ mol N m −2 h −1 ) compared to bare sediments (0.9–2 μ mol N m −2 h −1 ). Unusual pore‐water profiles in the macroalgal sediments suggest the presence of sulfur‐driven anoxic nitrification of NH 4 + to NO 3 − and N 2 . A benthic N budget showed that combined denitrification and coupled nitrification–denitrification accounted approximately 96% of the N 2 production, while DNRA accounted for 9% of total NO 3 − reduction pathways in the Noosa River Estuary. The macroalgae habitat contributed 76% of total N removal via N 2 production and 65% of N retention via DNRA, despite accounting for only 25% of the total surface area. We show a strong relationship between seagrass and macroalgae area and N 2 production ( r 2 = 0.8; p

Increasing temperature decreases the predatory effect of the intertidal shanny Lipophrys pholis on an amphipod prey - J. South; D. Welsh; A. Anton; J. D. Sigwart; J. T. A. Dick (Journal of Fish Biology, 2018)
Interactions between Lipophrys pholis and its amphipod prey Echinogammarus marinus were used to investigate the effect of changing water temperatures, comparing current and predicted mean summer temperatures. Contrary to expectations, predator attack rates significantly decreased with increasing temperature. Handling times were significantly longer at 19° C than at 17 and 15° C and the maximum feeding estimate was significantly lower at 19° C than at 17° C. Functional‐response type changed from a destabilizing type II to the more stabilizing type III with a temperature increase to 19° C. This suggests that a temperature increase can mediate refuge for prey at low densities. Predatory pressure by teleosts may be dampened by a large increase in temperature (here from 15 to 19° C), but a short‐term and smaller temperature increase (to 17° C) may increase destabilizing resource consumption due to high maximum feeding rates; this has implications for the stability of important intertidal ecosystems during warming events.

Niclosamide is a Negative Allosteric Modulator of Group I Metabotropic Glutamate Receptors: Implications for Neuropathic Pain - Ni Ai; Richard D. Wood; Eric Yang; William J. Welsh (Pharmaceutical Research, 2016)

Levels of Mercury in Feathers of Clapper Rails (Rallus crepitans) over 45 Years in Coastal Salt Marshes of New Hanover County, North Carolina - Auriel M.V. Fournier; Kyle James Welsh; Michael Polito; Steven D. Emslie; Rebecka Brasso (Bulletin of Environmental Contamination and Toxicology, 2016)

Holocene sea level instability in the southern Great Barrier Reef, Australia: high-precision U–Th dating of fossil microatolls - Nicole D. Leonard; J-x Zhao; K. J. Welsh; Y-x Feng; S. G. Smithers; J. M. Pandolfi; T. R. Clark (Coral Reefs, 2016)

Using passive acoustic telemetry to infer mortality events in adult herbivorous coral reef fishes - J. A. Khan; J. Q. Welsh; D. R. Bellwood (Coral Reefs, 2016)

Identification of Nitazoxanide as a Group I Metabotropic Glutamate Receptor Negative Modulator for the Treatment of Neuropathic Pain: An In Silico Drug Repositioning Study - Ni Ai; Richard D. Wood; William J. Welsh (Pharmaceutical Research, 2015)

Clustered parrotfish feeding scars trigger partial coral mortality of massive Porites colonies on the inshore Great Barrier Reef - J. Q. Welsh; R. M. Bonaldo; D. R. Bellwood (Coral Reefs, 2015)

Influence of sex and habitat on the size and shape of anal and dorsal fins of the blackstripe topminnow Fundulus notatus - D. P. Welsh; R. C. Fuller (Journal of Fish Biology, 2015)
The size and shape of the anal and dorsal fin in the blackstripe topminnow Fundulus notatus from lake and stream habitats across multiple ages and sexes were examined. Differences in the size and shape of anal and dorsal fins were sex‐specific and not related to habitat differences. Males have longer and more pointed anal fins and longer, larger and more pointed dorsal fins than females. These sex differences occur predominantly in the older age class. The angle ( i.e . pointedness) of the dorsal and anal fins is tightly correlated suggesting that fins follow a similar growth trajectory as individuals become sexually mature.

Herbivorous fishes, ecosystem function and mobile links on coral reefs - J. Q. Welsh; D. R. Bellwood (Coral Reefs, 2014)

Examining Two Different Approaches to Modelling Management and Operation Rules in a Single River System Model - Dushmanta Dutta; Jie Chen; Dave Penton; Matthew Bethune; Wendy D. Welsh; Shaun S. H. Kim; Tony Sheedy; Alistair Korn (Water Resources Management, 2014)

Evaluation of ionic liquids on phototrophic microbes and their use in biofuel extraction and isolation - Katherine S. Lovejoy; Lauren E. Davis; Lisa M. McClellan; Antonietta M. Lillo; John D. Welsh; Emily N. Schmidt; Claire K. Sanders; Alexander J. Lou; David T. Fox; Andrew T. Koppisch; Rico E. Del Sesto (Journal of Applied Phycology, 2013)

A Comparative Evaluation of Short-Term Streamflow Forecasting Using Time Series Analysis and Rainfall-Runoff Models in eWater Source - Dushmanta Dutta; Wendy D. Welsh; Jai Vaze; Shaun S. H. Kim; David Nicholls (Water Resources Management, 2012)

How far do schools of roving herbivores rove? A case study using Scarus rivulatus - J. Q. Welsh; D. R. Bellwood (Coral Reefs, 2012)

Detection of Neoparamoeba perurans by duplex quantitative Taqman real‐time PCR in formalin‐fixed, paraffin‐embedded Atlantic salmonid gill tissues - E Fringuelli; A W Gordon; H Rodger; M D Welsh; D A Graham (Journal of Fish Diseases, 2012)
The development and the application of a quantitative duplex real‐time PCR for the detection of Neoparamoeba perurans and the elongation factor α 1 gene (ELF) of Atlantic salmon, Salmo salar L., and rainbow trout, Oncorhynchus mykiss (Walbaum), are described. A set of primers and probe was designed to amplify a 139‐bp fragment specific to the N. perurans 18S rRNA gene. The test was shown to be very sensitive, being able to detect as little as 13.4 DNA copies per μL corresponding to 0.15 fg of template DNA. In addition, the reaction that detected N. perurans was found to have a high degree of repeatability and reproducibility, to have a linear dynamic range ( R 2 = 0.999) extending over 5 log 10 dilutions and to have a high efficiency (104%). The assay was applied to DNA samples extracted from 48 formalin‐fixed, paraffin‐embedded (FFPE) salmon gill tissues showing varying degrees of gill histopathology and amoebic gill disease (AGD)‐type histopathology ranging from absent to severe (each scored 0–3). Neoparamoeba perurans DNA was detected in all the blocks where AGD‐type histopathology was diagnosed microscopically and in 43.6% of the blocks showing signs of gill pathology. The association between parasitic load and gill histopathology and AGD‐type histopathology severity was also investigated. This study also describes the development and the application of a second real‐time PCR for the generic detection of Neoparamoeba spp ., Page, 1987. A set of primers and probe conserved among the Neoparamoeba spp. was designed to amplify a 150‐bp fragment within the 18S rRNA gene. Applied to N. perurans‐ negative gill tissues, the method was used to exclude the presence of other Neoparamoeba spp. in those blocks where gill pathology was observed microscopically.

Consensus Paper: Pathological Role of the Cerebellum in Autism - S. Hossein Fatemi; Kimberly A. Aldinger; Paul Ashwood; Margaret L. Bauman; Charles D. Blaha; Gene J. Blatt; Abha Chauhan; Ved Chauhan; Stephen R. Dager; Price E. Dickson; Annette M. Estes; Dan Goldowitz; et al. (The Cerebellum, 2012)

Performance of remote acoustic receivers within a coral reef habitat: implications for array design - J. Q. Welsh; R. J. Fox; D. M. Webber; D. R. Bellwood (Coral Reefs, 2012)

Spatial and temporal variation in coral predation by parrotfishes on the GBR: evidence from an inshore reef - R. M. Bonaldo; J. Q. Welsh; D. R. Bellwood (Coral Reefs, 2012)

Spatial ecology of the steephead parrotfish (Chlorurus microrhinos): an evaluation using acoustic telemetry - J. Q. Welsh; D. R. Bellwood (Coral Reefs, 2012)

Genetic diversity of Ovis aries populations near domestication centers and in the New World - H. D. Blackburn; Y. Toishibekov; M. Toishibekov; C. S. Welsh; S. F. Spiller; M. Brown; S. R. Paiva (Genetica, 2011)

In vitro culture of precision-cut testicular tissue as a novel tool for the study of responses to LH - Andy Michael Laughlin; Thomas H. Welsh; Charles C. Love; Dickson D. Varner; Alan R. Parrish; David W. Forrest; Nancy H. Ing (In Vitro Cellular & Developmental Biology - Animal, 2010)

Widespread occurrence and genetic diversity of marine parasitoids belonging to Syndiniales ( Alveolata ) - L. Guillou; M. Viprey; A. Chambouvet; R. M. Welsh; A. R. Kirkham; R. Massana; D. J. Scanlan; A. Z. Worden (Environmental Microbiology, 2008)
Summary Syndiniales are a parasitic order within the eukaryotic lineage Dinophyceae ( Alveolata ). Here, we analysed the taxonomy of this group using 43655 18S rRNA gene sequences obtained either from environmental data sets or cultures, including 6874 environmental sequences from this study derived from Atlantic and Mediterranean waters. A total of 5571 out of the 43655 sequences analysed fell within the Dinophyceae . Both bayesian and maximum likelihood phylogenies placed Syndiniales in five main groups (I–V), as a monophyletic lineage at the base of ‘core’ dinoflagellates (all Dinophyceae except Syndiniales ), although the latter placement was not bootstrap supported. Thus, the two uncultured novel marine alveolate groups I and II, which have been highlighted previously, are confirmed to belong to the Syndiniales . These groups were the most diverse and highly represented in environmental studies. Within each, 8 and 44 clades were identified respectively. Co‐evolutionary trends between parasitic Syndiniales and their putative hosts were not clear, suggesting they may be relatively ‘general’ parasitoids. Based on the overall distribution patterns of the Syndiniales ‐affiliated sequences, we propose that Syndiniales are exclusively marine. Interestingly, sequences belonging to groups II, III and V were largely retrieved from the photic zone, while Group I dominated samples from anoxic and suboxic ecosystems. Nevertheless, both groups I and II contained specific clades preferentially, or exclusively, retrieved from these latter ecosystems. Given the broad distribution of Syndiniales , our work indicates that parasitism may be a major force in ocean food webs, a force that is neglected in current conceptualizations of the marine carbon cycle.

Relationship Between the Endophyte Embellisia spp. and the Toxic Alkaloid Swainsonine in Major Locoweed Species (Astragalus and Oxytropis) - M. H. Ralphs; R. Creamer; D. Baucom; D. R. Gardner; S. L. Welsh; J. D. Graham; C. Hart; D. Cook; B. L. Stegelmeier (Journal of Chemical Ecology, 2008)

Effect of Ractopamine HCl Supplementation on Fecal Shedding of Escherichia coli O157:H7 and Salmonella in Feedlot Cattle - T. S. Edrington; T. R. Callaway; S. E. Ives; M. J. Engler; T. H. Welsh; D. M. Hallford; K. J. Genovese; R. C. Anderson; D. J. Nisbet (Current Microbiology, 2006)

The effect of postural stability and spatial orientation of the upper limbs on interlimb coordination - Timothy N. Welsh; Quincy J. Almeida; Timothy D. Lee (Experimental Brain Research, 2005)

Bacterial nitrification activity directly associated with isolated benthic marine animals - D. T. Welsh; G. Castadelli (Marine Biology, 2004)

Influence of terminal action requirements on action-centered distractor effects - P. L. Weir; D. J. Weeks; T. N. Welsh; D. Elliott; R. Chua; E. A. Roy; J. Lyons (Experimental Brain Research, 2003)

Distribution of Locoweed Toxin Swainsonine in Populations of Oxytropis lambertii - M. H. Ralphs; S. L. Welsh; D. R. Gardner (Journal of Chemical Ecology, 2002)

Denitrification in an intertidal seagrass meadow, a comparison of 15 N-isotope and acetylene-block techniques: dissimilatory nitrate reduction to ammonia as a source of N 2 O? - Welsh D.; Castadelli G.; Bartoli M.; Poli D.; Careri M.; R. de Wit; Viaroli P. (Marine Biology, 2001)

Copper, Cadmium, and Zinc Concentrations in Juvenile Chinook Salmon and Selected Fish-Forage Organisms (Aquatic Insects) in the Upper Sacramento River, California - Michael K. Saiki; Barbara A. Martin; Larry D. Thompson; Daniel Welsh (Water, Air, & Soil Pollution, 2001)

Isolation of salmon pancreas disease virus (SPDV) from farmed Atlantic salmon, Salmo salar L., in Scotland - H. M. Rowley; C. E. Doherty; M. F. McLoughlin; M. D. Welsh (Journal of Fish Diseases, 1998)
A toga‐like virus was recently isolated in the present authors' laboratory from Atlantic salmon during an outbreak of PD in Ireland (Nelson, McLoughlin, Rowley, Platten & McCormick 1995). When inoculated into Atlantic salmon post‐smolts, this virus, known as salmon pancreas disease virus (SPDV), caused pathological changes in the pancreas, heart and skeletal muscle which were indistinguishable from those observed in natural outbreaks of PD (McLoughlin, Nelson, Rowley, Cox & Grant 1996). In 1996 a serological survey was carried out to determine the presence and distribution of antibodies to SPDV in Irish, Scottish and Norwegian farm‐reared Atlantic salmon (McLoughlin, Rowley & Doherty 1998). The results of this survey indicated that SPDV is present in the major European salmon‐producing countries. The present paper describes the first isolation of SPDV from farm‐reared, PD‐affected Atlantic salmon in Scotland.

HLA-DRB1 amino acid disparity is the major stimulus of interleukin-2 production by alloreactive helper T-lymphocytes - N. T. Young; D. L. Roelen; Margaret J. Dallman; Peter J. Morris; Ken I. Welsh (Immunogenetics, 1998)

Contaminants in eggs of aquatic birds from the Grasslands of Central California - R.L. Hothem; D. Welsh (Archives of Environmental Contamination and Toxicology, 1994)

Concentrations of selenium in biota, sediments, and water at Cibola National Wildlife Refuge - D. Welsh; O. E. Maughan (Archives of Environmental Contamination and Toxicology, 1994)